Fake News – The case of microwave cooking (Research, Society and Development, 2021)
The information freely conveyed by social media is not committed to ethics, morals or any theoretical or scientific principles. This information can become a serious social problem when using false content to manipulate public opinion. If we consider that democracy and freedom are built with individuals who make conscious choices, the fake news, as it became known, must be fought. In this context, this article presents and discusses, in the light of scientific knowledge, the main information conveyed about microwave cooking between August 2020 and February 2021 by social media as a proposal to combat fake News. The results show that classifying news as false or true is not a simple task. This is because fake news tries to sensitize the reader and reinforce common sense ideas. Thus, we defend scientific literacy, as a result of an efficient teaching-learning process, as a possible way to fight fake News.